Structural static and modal frequency simulations in a coffee harvester’s chassis - Evandro P. da Silva; Fábio M. da Silva; Ednilton T. de Andrade; Ricardo R. Magalhães (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Coffee harvesters are subject to stresses and vibrations in their structure, originating from engines and harvesting system. These structures must be designed to avoid rupturing of the components due to fragility of the materials, inadequate geometries, or the phenomenon of resonance, which increases the displacements/deformations of the components. In this scenario, the main objective of this study is to analyse the results of stresses and displacements from two static simulations and to present results of natural vibration frequencies from two modal simulations in a self-propelled coffee harvester. For this purpose, 20 modal shapes were generated, considering coffee harvester reservoir as empty and full. The simulations were carried out using the finite element method in which actual boundary conditions were applied to the motor chassis of the harvester. As results, stresses above the material’s yield strength were observed in some regions of the components. Greater displacements were observed at the rear of the chassis, suggesting a new positioning of the rear wheel to obtain a uniform load distribution. Some natural frequencies, which presented greater displacements/deformations, can be affected by the operation of the main motor, also associated with the vibrating system in the coffee harvest, which may cause rupture of components.